Sportorthopädie - Drews BH; Mauch F (Dynamic Media Sales Verlag, 2017)
Treatment of sports injuries needs effective and early diagnostics to provide optimal therapy and return-to-sports with a minimum of delay. Patient history and clinical examination determine order and urgency of further imaging tools. Usually, sonography (US) is the first-line diagnostic tool to detect muscle-, tendon- and peripheral ligamentous injuries. It gives the opportunity to differentiate acute lesions from chronic overuse injuries. Furthermore, in frequent follow-up examinations after an acute injury it is of great value to monitor the healing process. Advantages, especially towards magnetic resonance imaging (MRI), are early availability (in part already sidelines or in the changing room with portable devices), low costs and the possibility of dynamic examination (e.g. in tendon ruptures or ligament injuries). The latter is one of the most important benefits towards static MRI,as partial lesions can be detected easily. Furthermore, influence of the injuries onfunction and stability can be evaluated in real-time. Besides, technical advancements like Contrast-enhanced Ultrasonography (CEUS), Elastography and Ultrasonographic Tissue Characterization (UTC) might improve sonographic sensitivity and expand therange of application in the near future. Although, magnetic resonance imaging (MRI) is increasingly available and used more and more for primary diagnostics, US remains one of the most important tools in the hands of sports medicine specialists.KEY WORDS: Sonography, Ultrasound, Sports Injury, Diagnostics